Communicating about Mental Health with Youth and Their Families: A Scoping Review of Best Practices and Implications for Youth with Disabilities. (3rd April 2022) - Bonder, Revi; Yonadam, Arbella; Snider, Andrea; Kassam-Lallani, Dilshad; McPherson, Amy C.
ABSTRACT: Minimal attention has been placed on supporting the mental health needs of youth with disabilities. Due to a dearth of research on best practices in mental health communication with youth with disabilities, the aim of the scoping review was to identify existing peer-reviewed evidence regarding mental health communication for the general youth population in clinical settings. Three electronic databases were searched. Inclusion criteria were: 1) published in English between 2009 and 2019; 2) children and youth and/or their parents/caregivers; 3) addressed communication-based mental health practices; 4) based in pediatric health care settings. Seven articles were included. Promoting autonomy and engagement, building collaboration and trust, and supplementing conversations with alternative communication approaches were identified as important for having mental health conversations. While implications can be drawn, more work is needed for clinicians to have a rigorous evidence base to draw upon when having these conversations with youth with disabilities.